Liquid Metal Based Island‐Bridge Architectures for All Printed Stretchable Electrochemical Devices - Silva, Cristian A.; lv, Jian; Yin, Lu; Jeerapan, Itthipon; Innocenzi, Gabriel; Soto, Fernando; Ha, Young‐Geun; Wang, Joseph (Advanced functional materials, 2020)
The adoption of epidermal electronics into everyday life requires new design and fabrication paradigms, transitioning away from traditional rigid, bulky electronics towards soft devices that adapt with high intimacy to the human body. Here, a new strategy is reported for fabricating achieving highly stretchable “island‐bridge” (IB) electrochemical devices based on thick‐film printing process involving merging the deterministic IB architecture with stress‐enduring composite silver (Ag) inks based on eutectic gallium‐indium particles (EGaInPs) as dynamic electrical anchors within the inside the percolated network. The fabrication of free‐standing soft Ag‐EGaInPs‐based serpentine “bridges” enables the printed microstructures to maintain mechanical and electrical properties under an extreme (≈800%) strain. Coupling these highly stretchable “bridges” with rigid multifunctional “island” electrodes allows the realization of electrochemical devices that can sustain high mechanical deformation while displaying an extremely attractive and stable electrochemical performance. The advantages and practical utility of the new printed Ag‐liquid metal‐based island‐bridge designs are discussed and illustrated using a wearable biofuel cell. Such new scalable and tunable fabrication strategy will allow to incorporate a wide range of materials into a single device towards a wide range of applications in wearable electronics. Liquid metal based materials offer distinct advantages for the fabrication of island‐bridge electrochemical electronics. This study describes a novel approachmerging the unique advantages of deterministic architectures with stress‐enduring nanoengineered inks, supported with dynamic electrical anchors inside the percolated network. Versatile applications with various functional materials are also demonstrated by printing epidermal biofuel cells tested successfully on human subjects.